Search for the production of an excited bottom quark decaying to tW in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2016)
A search is presented for a singly produced excited bottom quark (b*) decaying to a top quark and a W boson in the all-hadronic, lepton+jets, and dilepton final states in proton-proton collisions at root s = 8 TeV recorded by the CMS experiment at the CERN LHC. Data corresponding to an integrated luminosity of 19.7 fb(-1) are used. No significant excess of events is observed with respect to standard model expectations. We set limits at 95% confidence on the product of the b* quark production cross section and its branching fraction to tW. The cross section limits are interpreted for scenarios including left-handed, right-handed, and vector-like couplings of the b* quark and are presented in the two-dimensional coupling plane based on the production and decay coupling constants. The masses of the left-handed, right-handed, and vector-like b* quark states are excluded at 95% confidence below 1390, 1430, and 1530 GeV, respectively, for benchmark couplings. This analysis gives the most stringent limits on the mass of the b* quark to date.
Keywords: Jet substructure; Hadron-Hadron scattering; Beyond Standard Model